Czarnogóra i Bośnia-Hercegowina (problemy graniczne i etniczne) - Kałążna, Klaudia; Rosicki, Remigiusz (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
The borderline between Montenegro and Bosnia-Heregovina is an outcome of numerous factors: firstly – religion, secondly – ethnic composition, thirdly – politics, and finally – geographical conditions. The stronger influence of the Orthodox Church in Montenegro and Serbia resulted in the survival and relative cohesion of the respective populations of both countries. This has not occurred in Bosnia-Herzgovina. This state is a product of political agreements on the internal and international levels. This may be exemplified by the so-called Serbian Republic that me the eastern frontier of the country. Thus the Serbian Republic constitutes the border with Montenegro. The contemporary territory of the Republic does not proportionately reflect the ethnic composition (Serbian minority).